Evaluation of the Bond Strength of Self-Etching Adhesive Systems Containing HEMA and 10-MDP Monomers: Bond Strength of Adhesives Containing HEMA and 10-MDP - Roberta Pimentel de Oliveira; Brennda Lucy de Paula; Mara Eliane Ribeiro; Eliane Alves; Hilton Túlio Costi; Cecy Silva (International Journal of Dentistry)
The aim of this in vitro study was to assess the bond strength of self-etching adhesives containing HEMA and 10-MDP monomers. Twenty-four bovine teeth were divided into three groups. Two cylinders of composite resin were made in each tooth (n = 16): G1-Prime and Bond Universal (control); G2-OptiBond All-in-One (HEMA); and G3-Clearfil SE (10-MDP and HEMA). After 24-hour storage in distilled water, the specimens were fixed to a universal testing machine (Kratos Equipamentos Ltda.) for the microshear test at a speed of 0.5 mm/min. A qualitative analysis of the fracture pattern was also performed using scanning electron microscopy (500× magnification). The normality of sample data distribution was determined using the Shapiro–Wilk test. The results were assessed using the Kruskal–Wallis test, and α level of 5% was used for the analysis. The results indicated a statistical difference (p>0.05) between G3 (15.6080 MPa) and G2 (11.2180 MPa). No statistical difference was observed when G1 (14,6325 MPa) was compared with the other two groups. It was also observed that a mixed fracture pattern was predominant in all groups. The self-etching adhesive containing HEMA and 10-MDP monomers showed to be promising in increasing the bond strength between the dental substrate and the composite resin, whereas the adhesive containing only HEMA exhibited lower bond strength to dentin.